Cancer-Attributable Mortality among Solid Organ Transplant Recipients in the United States, 1987-2014 - Noone, Anne-Michelle (Cancer, 2019)
BACKGROUND: Solid organ transplant recipients have an elevated risk of cancer. Quantifying deaths attributable to cancer can inform priorities to reduce cancer burden. METHODS: Linked transplant and cancer registry data were used to identify incident cancers and deaths among solid organ transplant recipients in the United States (1987–2014). Population-attributable fractions (PAFs) of deaths due to cancer and corresponding cancer-attributable mortality rates were estimated using Cox models. RESULTS: Among 221,962 transplant recipients, 15,012 developed cancer. Thirteen percent of deaths (PAF=13.2%) were attributable to cancer, corresponding to a cancer-attributable mortality rate of 516 per 100,000 person-years. Lung cancer was the largest contributor to mortality (PAF=3.1%), followed by non-Hodgkin lymphoma (NHL, PAF=1.9%), colorectal cancer (PAF=0.7%), and kidney cancer (PAF=0.5%). Cancer-attributable mortality rates increased with age at transplantation, reaching 1229 per 100,000 person-years among recipients 65+ years old. NHL was the largest contributor among children (PAF=4.1%) and lung cancer among 50+ year-olds (PAFs=3.7–4.3%). Heart recipients had the highest PAF (16.4%), but lung recipients had the highest cancer-attributable mortality rate (1241 per 100,000 person-years). Overall, mortality attributable to cancer increased steadily with longer time since transplant, reaching 15.7% of deaths (810 per 100,000 person-years) 10+ years post-transplant. Comparison of cancer-attributable mortality rates with specified causes of death indicated that some deaths recorded as other causes might instead be caused by cancer or its treatment. CONCLUSIONS: Cancer is a substantial cause of mortality among solid organ transplant recipients, with major contributions from lung cancer and NHL. Cancer-attributable mortality increases with age and time since transplant, so cancer deaths will become an increasing burden as recipients live longer.